Gambaran Asupan Zat Gizi dan Prestasi Belajar pada Siswa Stunting di Yayasan Pendidikan SMP Swasta Anugerah Sitinjo Kabupaten Dairi Tahun 2017 - Nenny Rotua Cibro; Fitri Ardiani; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Stunting case in school-age children is a manifestation from stunting in toddler, because there is no improvement on catch up growth intake of macro and micro nutrients which is not accordance with long term needs. This research aims to know the description intake of nutrients and academic achievement of stunting students in Yayasan Pendidikan SMP Swasta Anugerah Sitinjo Kabupaten Dairi years 2017. This study is a descriptive research with cross sectional study design. This study doing by calculating energy, protein, vitamin A, calcium, phosphorus and iron intake by using 24 hours food recall method and food frequency form, and academic achievement calculating by the value of the report cards. This sample of research is all stunting students as many as 63 students. The result of this study show that intake of nutrients of stunting students in Yayasan Pendidikan SMP Swasta Anugerah Sitinjo Kabupaten Dairi according to the amount of food based on the macro nutrients intake namely energy and protein intake classified deficient, and micro nutrients intake namely vitamin A, calcium, phosphorus and iron classified deficient. According to the type of food  consumed an avarage of 2 types per day and most of the stunting students consume rice as a staple food, fish and eggs as a side dish. From the academic achievement, stunting students is in good chategory. The suggested is the school cooperate with the primary health care to gives nutritional education to children and to stunting students expected to consume complete food sources of nutrients every day suitable with the amount and the type of food to be able to catch up the growth. Keywords: nutrients intake, students academic achievement, stunting.